Impact of pulse pressure on clinical outcome in extracorporeal cardiopulmonary resuscitation (eCPR) patients. (14th October 2021) - Rilinger, J; Riefler, A M; Bemtgen, X; Jaeckel, M; Zotzmann, V; Biever, P M; Duerschmied, D; Benk, C; Trummer, G; Kaier, K; Bode, C; Staudacher, D L; et al.
Abstract: Background: Hemodynamic response after successful extracorporeal cardiopulmonary resuscitation (eCPR) is very heterogeneous. Pulse pressure (PP) as an easy to access surrogate parameter and correlate for myocardial damage or recovery from it, might be a valuable tool to estimate the outcome of these patients. Purpose: To investigate the predictive value of the surrogate parameter PP in eCPR patients. Methods: We report retrospective data of a single-centre registry of eCPR patients, treated at our Interdisciplinary Medical Intensive Care Unit between 01/2017 and 01/2020. The association between PP of the first 10 days after eCPR and hospital survival was investigated. Moreover, patients were divided into three groups according to their PP (low (0–9 mmHg), mid (10–29 mmHg) and high (≥30 mmHg)) at each time point. Results: 143 patients (age 63 years, 74.1% male, 40% OHCA, average low flow time 49 min) were analysed. Overall hospital survival rate was 28%. A low PP both early after eCPR (after 1, 3, 6 and 12 hours) and in the further course after day 1 to day 8 was associated with reduced hospital survival. At each time point (1 hour to day 5) the classification of patients into a low, mid and high PP group was able to categorize the patients for a low (5–20%), moderate (20–40%) and high (50–70%) survival rate. A multivariable analysis showed that the mean PP of the first 24 hours was an independent predictor for survival (p=0.008, figure 1). Conclusion: In this analysis, PP occurred to be a valuable parameter to estimate survival and maybe support clinical decision making in the further course of patients after eCPR. Funding Acknowledgement: Type of funding sources: None.